Estrutura vertical da atmosfera em Belém - PA no mês de novembro em anos de contraste (seco e chuvoso) - ANANIAS, Daniela dos Santos (2019)
Based on 26-years (1982-2007) data set, a diagnostic study on the vertical structure of air temperature, dew point temperature and relative humidity observed over Belém-PA, during the months of November, is presented in this work. The analysis were conducted for two contrasting composites considering the precipitation regime: the rainy years and of dry years, which were established objectively using percentiles method. Overall, the composites demonstrated that the temperature and moisture profiles are abnormally warmer (colder) and wetter (drier) in association with the rainfall above (below) of normal in the Belém region. The results showed that the main difference in profiles studied, comparing wet and dry years, occurs in the atmospheric layer between the tropospheric medium and high levels (between the 700 hPa and 400 hPa patterns pressure levels). In this layer, the difference between air temperature, dew point and moisture is significantly higher associated with enhanced convection and precipitation.